2013
DOI: 10.1128/jcm.02234-12
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of OXA-48 and OXA-181 Carbapenemases among Enterobacteriaceae in South Africa and Evidence of In Vivo Selection of Colistin Resistance as a Consequence of Selective Decontamination of the Gastrointestinal Tract

Abstract: This study reports on the emergence of OXA-48-like carbapenemases among isolates of Enterobacteriaceae in South Africa. In addition, the emergence during therapy of a colistin-resistant OXA-181-producing Klebsiella pneumoniae isolate was documented following selective digestive tract decontamination with oral colistin, which is therefore strongly discouraged. CASE REPORTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
76
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 19 publications
3
76
0
2
Order By: Relevance
“…In Africa, the bla OXA-181 gene has only been reported in Angola (Kieffer et al, 2016) and South Africa (Brink et al, 2013). However, it has also been detected together with the NDM-1 and VIM-2 carbapenemase genes in a surveillance rectal swab isolate obtained from a patient in Canada who had previously been hospitalized in Nigeria (Walkty et al, 2015).…”
mentioning
confidence: 99%
“…In Africa, the bla OXA-181 gene has only been reported in Angola (Kieffer et al, 2016) and South Africa (Brink et al, 2013). However, it has also been detected together with the NDM-1 and VIM-2 carbapenemase genes in a surveillance rectal swab isolate obtained from a patient in Canada who had previously been hospitalized in Nigeria (Walkty et al, 2015).…”
mentioning
confidence: 99%
“…Resistance to the clinically significant carbapenem antibiotics by enzymatic hydrolysis has been described in Enterobacteriaceae worldwide, and recently the class D β-lactamase, OXA-48 and its variants have been detected more frequently. [4] While the bla OXA-181 gene has previously been identified in several clonally unrelated K. pneumoniae isolates from SA, India, Singapore, the Netherlands and New Zealand, [4][5][6][7][8][9][10][11][12] this is the first report describing an outbreak of bla OXA-181 in SA. To our knowledge this is the first identification of a bla OXA-181 -producing K. oxytoca isolate.…”
Section: Discussionmentioning
confidence: 93%
“…[3] OXA-48 was first described in the environmental bacterium Shewanella spp., and more recently there have been several reports of this enzyme, mainly in K. pneumoniae isolates, from countries in the Middle East, Europe, and northern and southern Africa. [4][5][6][7] OXA-181, a variant of OXA-48, was first identified in K. pneumoniae isolated from a Tanzanian patient. [7] It differs by just four amino acid substitutions in the active site, yet still confers the same levels of enzymatic hydrolysis of carbapenems as OXA-48.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated emergence of resistance during CRE decolonisation regimens (which usually include colistin), [30][31][32] and this, allied to limited evidence of its efficacy, strongly suggests that decolonisation for multiresistant Gram-negative bacteria should not be attempted. If active screening for CRE carriage is carried out, the main intervention for carriers consists of isolation/cohorting and enhanced infection control measures.…”
Section: Screening and Decolonisationmentioning
confidence: 99%